2020
DOI: 10.1139/cgj-2019-0326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of capillary water retention effects on the development of the suction stress characteristic curve

Abstract: The suction stress characteristic framework is a practical approach for relating the suction and the water-filled pore volume to the stress state of unsaturated soils. It predicts the effective stress by developing the suction stress characteristic curve from the soil-water retention curve. In this framework, the effective degree of saturation is usually calculated by the empirical water retention model of van Genuchten (published in 1980). In this paper, the use of a generalized soil-water retention model pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Consequently, the water-retention characteristics improve [52]. The main factors affecting the total soil suction are capillary action [53,54], short-range adsorption (interaction between particles and pore water) [55], and infiltration [56]. The foregoing analysis indicates that fibres affect the water-retention characteristics of soil.…”
Section: Swcc Model Considering Fibre Reinforcementmentioning
confidence: 99%
“…Consequently, the water-retention characteristics improve [52]. The main factors affecting the total soil suction are capillary action [53,54], short-range adsorption (interaction between particles and pore water) [55], and infiltration [56]. The foregoing analysis indicates that fibres affect the water-retention characteristics of soil.…”
Section: Swcc Model Considering Fibre Reinforcementmentioning
confidence: 99%
“…This means that the numerous larger pores easily released most of the capillary water at low suction values thereby governing the initial portion of the curve from 0.1 kPa to 700 kPa. Conversely, the fewer smaller pores released the remainder of capillary water and part of the adsorbed water only with the application of high suction values, that is, in the range of 700 kPa to 10 6 kPa [68]. Irrespective of the index property on the y-axis, the WRC comprised two air entry values and two residual suction values associated with capillary water drainage [69,70]: from larger pores (AEVL = 2 kPa and RSVL = 20 kPa) and from smaller pores (AEVS = 700 kPa and RSVS = 5 × 10 4 kPa).…”
Section: Water Retentionmentioning
confidence: 99%
“…This means that the numerous larger pores easily released most of the capillary water at low suction values thereby governing the initial portion of the curve from 0.1 kPa to 700 kPa. Conversely, the fewer smaller pores released the remainder of capillary water and part of the adsorbed water only with the application of high suction values, that is, in the range of 700 kPa to 10 6 kPa [68].…”
Section: Volumetric Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, stresses in soil reflect the mechanical energy per unit volume of the soil-water-air mixture." That is presumably why many researchers have previously suggested that capillary water, solely, plays a role in the mechanical behavior of unsaturated soils (Konrad and Lebeau 2015;Zhou et al 2018;Maleksaeedi and Nuth 2019). In fact, Lu et al (2010) argued that "the residual water content is the amount of water that remains primarily in the form of thin films surrounding the soil particle surfaces at very high suctions but has very little effect on the interparticle suction stress."…”
mentioning
confidence: 99%